Efficacy of Philosophy Training for Children on the Social Responsibility and Ethical Intelligence of 9-12-Year-Old Children - Zeinab Ghdiri Bidhendi; Seyyed Mahmoud Mirzamani Bafghi (پژوهش‌های کاربردی روانشناختی)
The present study was conducted to investigate the efficacy of philosophy training for children in fostering social responsibility and ethical intelligence in 9-12-year-old children. The present study was quasi-experimental with pretest, posttest and control group design method. Additionally, a two-month follow-up period was implemented. The statistical population of the current survey consisted of 9-11-year-old children residing in Tehran during the academic year 2021-2022. The purposive sampling method was employed to select thirty-two girls with low social responsibility and ethical intelligence. The girls were randomly assigned to the experimental and control groups, with 17 children in the experimental group and 15 in the control group. Eight 60-minute sessions of training philosophy for children were administered to the experimental group’s children. The questionnaires that were implemented were the Social Responsibility Questionnaire (SAQ) and the Ethical Intelligence Questionnaire (EIQ). The collected data were analyzed through mixed ANOVA and Bonferroni test via SPSS23 software. The results showed that the instruction of children in philosophy has a significant effect on social responsibility (F=36.30, Eta-0.55, P<0.001) and ethical intelligence (F=55, Eta=0.64, P<0.001). According to the findings of the study it can be concluded that training philosophy for children can be used as an efficient method to improve the children’s social responsibility and ethical intelligence through employing deep conversation and creating internal empowerment in the child.